2013
DOI: 10.1037/a0033127
|View full text |Cite
|
Sign up to set email alerts
|

Initial validation of a new measure of leadership.

Abstract: In recent years, theorists and practitioners have become critical of the popular conceptualization of leadership as composed of task and relationship types of behaviors for two reasons: (a) other leadership behaviors, such as creating a mission and vision and employee empowerment, are not included in this conceptualization, and (b) under a strict definition of leadership, task-oriented behaviors are more "management" than truly "leadership" behaviors. Gill's (R. Gill, 2006, Theory and Practice of Leadership, T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 51 publications
1
9
0
Order By: Relevance
“…It is also worth noting that assessments of leadership was the single strongest unique predictor of work engagement. This is consistent with the results observed by Rupprecht et al (2013) and Choi et al (2015). Given all the disruption caused by the pandemic, many workers obviously benefited in terms of their work engagement when they perceived their supervisor to be a more effective leader, potentially because as Arnold et al (2007), they help workers see meaning in the work they do.…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…It is also worth noting that assessments of leadership was the single strongest unique predictor of work engagement. This is consistent with the results observed by Rupprecht et al (2013) and Choi et al (2015). Given all the disruption caused by the pandemic, many workers obviously benefited in terms of their work engagement when they perceived their supervisor to be a more effective leader, potentially because as Arnold et al (2007), they help workers see meaning in the work they do.…”
Section: Discussionsupporting
confidence: 86%
“…Remote learning and working experiences were assessed with seven items from Staples et al (1999) adapted to assess remote work training (e.g., Leadership Behaviors -Assessment of Supervisor. Participants' perceptions of their direct supervisor's leadership behaviors were measured with the General Inventory for Lasting Leadership (GILL; Rupprecht et al, 2013). The 39-item GILL is based upon Gill's (2006) conceptualization of leadership, containing five dimensions: vision and mission, strategy, empowerment; influence, motivation, and inspiration; and shared values.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies (Fritz et al, 2013;Rupprecht, Waldrop, & Grawitch, 2013) have shown correlation between certain qualities and behaviors of a leader and employee commitment to mission. To better understand employees' mission ownership, which might be influenced by their leader, it is important to look at how employees view the source of mission.…”
Section: Mission and Vision From The Cco Perspectivementioning
confidence: 94%
“…The vast majority of this work centers on the leader's role in developing and implementing mission (e.g., Rupprecht, Waldrop, & Grawitch, 2013) and vision (e.g., Sosik & Dinger, 2007). The vast majority of this work centers on the leader's role in developing and implementing mission (e.g., Rupprecht, Waldrop, & Grawitch, 2013) and vision (e.g., Sosik & Dinger, 2007).…”
mentioning
confidence: 99%